LAYANAN BIMBINGAN KLASIKAL KELAS X SMA MUJAHIDIN PONTIANAK - Muhammad Rian Andani; Indri Astuti; Yuline Yuline (Universitas Tanjungpura, 2019)
AbstractClassic guidance service is one form of assistance for guidance and counseling services for students conducted in class format. The general problem of this research is